Profesionalisme Pendidik: Ikhtiar dan Tantangan Pasca Disyahkannya UU RI Nomor 14 Tahun 2005 - rahman afandi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Â profession means an occupation that requires a qualification of education, skill, and standardization. As well, a profession also requires social responsibility. Therefore, a teacher as a professional worker has to have a qualification of education so that he can properly does his/her duty and function. In other words, a professional teacher is one that well educated and trained on his/her subject. In detail, a teacher (to some extent including a lecturer) must have proper education concerning on his/her subject, good academic capability, faith and piety, good character, and good emotional and social intelligence. .